2021
DOI: 10.1007/s12665-021-09376-1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of diagenetic alterations and mechanical properties of Lower Permian siliciclastic sandstones: a pilot study

Abstract: Initial detrital composition and authigenic alterations during diagenesis of three sandstone types are related to their mechanical properties. Sandstones were prepared for geotechnical standard tests [density, uniaxial compressive strength (UCS), Young’s modulus (E), strain at failure (ε)] and thin sections for petrographic analyses (point counting). UCS ranges from 3 to 62 MPa and positively correlates with density (1.75–2.35 g/cm3) and E (0.3–12.7 GPa). Optical porosity is controlling these mechanical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…North Sea Chalk is the overburden rock for the Britannia and Goldeneye Fields.The properties used in table 3 are derived from the ‘Overall Range’ column herein.References from which each property was extracted were: true0Eres—Monsees et al . [68], Camm et al . [69], Shell [70]; true0Kres—Hillier [71], Camm et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…North Sea Chalk is the overburden rock for the Britannia and Goldeneye Fields.The properties used in table 3 are derived from the ‘Overall Range’ column herein.References from which each property was extracted were: true0Eres—Monsees et al . [68], Camm et al . [69], Shell [70]; true0Kres—Hillier [71], Camm et al .…”
Section: Methodsmentioning
confidence: 99%
“…References from which each property was extracted were: true0Eres—Monsees et al . [68], Camm et al . [69], Shell [70]; true0Kres—Hillier [71], Camm et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rakshit et al (2021) while investigating the influence of micromechanical properties of sandstones of Western Indo-Burmese Ranges, Northeast India, opined their strength reduction to be a result of the presence of angular and semi-angular spherical grains. Similarly, Monsees et al (2021) while investigating the relationship between diagenetic alteration and mechanical properties of Permian Siliciclastic sandstones suggested optical porosity which was linked to diagenetic alteration as a significant factor influencing its mechanical properties. Wang et al (2019) who observed the failure modes for three types of sandstones noticed the destruction of the sandstone with the highest strength before the mudstone interface.…”
Section: Introductionmentioning
confidence: 96%